2015
DOI: 10.1074/jbc.m115.659466
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacterial Pathogens Trigger the Formation of U Small Nuclear RNA Bodies (U Bodies) through Metabolic Stress Induction

Abstract: Background:The impact of metabolic stress on host response to bacterial infection remains poorly characterized. Results: Intracellular bacteria (Shigella, Salmonella, and Listeria) induce cytoplasmic U bodies through metabolic stress. Conclusion: Bacterial infection and metabolic stress affect the splicing machinery. Significance: Regulation of U snRNA maturation is a novel checkpoint in innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 46 publications
6
26
0
Order By: Relevance
“…5e and Additional file 5: Figure S3E), providing further support for our results that identified a key role for metabolic stress stimuli in the dynamic regulation of the splicing machinery [19]. …”
Section: Resultssupporting
confidence: 85%
“…5e and Additional file 5: Figure S3E), providing further support for our results that identified a key role for metabolic stress stimuli in the dynamic regulation of the splicing machinery [19]. …”
Section: Resultssupporting
confidence: 85%
“…A similar temporal shift in sizes was observed for snRNA: at 2 hrs, the differentially-expressed snRNAs were mostly RNU6 pseudogenes, an abundant class of snRNA with unknown function; while at 6 and 24 hrs, the down-regulated snRNA were larger and consisted mostly of the snRNA building blocks of the major and minor spliceosomes. These snRNAs have been previously shown to be down-regulated in response to intracellular infection with Shigella , which affected spliceosomal snRNA maturation, dependent on the activation of a metabolic stress pathway [29]. Our studies suggest the possibility of a similar effect in response to Pseudomonas infection, and the altered expression of the major and minor spliceosome components could possibly influence alternative splicing, as previously suggested [30].…”
Section: Discussionsupporting
confidence: 80%
“…By text mining with the stress signatures identified in the SMA models described here, we found that mutations in the Activating transcription factor 3 (Atf3) gene cause a similar dysregulation in immune and metabolic homeostasis (Rynes et al 2012). Among other things, this signaling pathway appears to regulate the cytosolic formation of SMN-containing U-bodies in human cells in response to bacterial pathogens (Tsalikis et al 2015). If SMN does indeed intersect with a normal host cell response to bacteria, this would provide a parsimonious model for the activation of stress signaling in SMA models, and another avenue to explore potential connections to neuromuscular disease.…”
Section: Rna Signatures Of Diseasementioning
confidence: 99%